Incidental consumption of plastic and other anthropogenic materials by Coragyps atratus (Bechstein, 1793) in a garbage dump in Ecuador - Richard, Enrique (2021)
This study analyzes and discusses the ingestion of plastic and other anthropogenic materials by Coragyps atratus in a suburban waste dump in Calceta, Manabí Province, Ecuador. Of a total of 112 pellets analyzed, 100% contained anthropogenic materials, the most conspicuous being different types of plastics and microplastics, as well as metals, glass, soil, and others. The relative importance of the anthropogenic materials found is discussed and analyzed, same as their potential impact on the species and humanity.